Cold direct pen writing of reduced graphene oxide foams for ultrasensitive micro-contact force probing. (February 2020) - Chai, Yuqiao; Ma, Xinlei; Zang, Xiaoling; Wang, Xusheng; Zhu, Nan; Xie, Zhuang; Ji, Junhui; Zhang, Xueji; Xue, Mianqi
Abstract: Pressure sensor has attracted great attention due to its wide applications in electronic skin, health monitor, and wearable devices. However, there is still an urgent challenge in sensing the weak force, especially in the micro-contact cases. Herein, a novel cold direct pen writing method has been developed for fabricating reduced graphene oxide microfoam (rGOMF) as a pressure sensing element. The as-fabricated rGOMF-based pressure sensor exhibits ultrahigh sensitivities of 0.19, 0.82, and 1.43 KPa −1 in the pressure ranges of 0–10, 10–25 and 25–40 Pa with a micro-contact area of 0.594 mm 2, respectively, which satisfies the ultrasensitive probing of micro-contact force. Meanwhile, it shows a high stability over 1000 cycles of pressure testing with a fast response (100 ms) and high reversibility. Not limited to rGO, this method is also suitable for other two-dimensional nanomaterials. Thus, this approach is anticipated to be applied to a wide range of microfoam-based devices with advanced functions such as multifunctional sensing, water separation, energy conversion and storage. Graphical abstract: Image 1